Association of Physical Activity and Fruit-Vegetable Consumption with Nutritional Status among Adolescent Girls - Hikmawati Mas'ud; St. Nur Rismayanti; Abdullah Tamrin; Mustamin Mustamin (Direktorat Politeknik Kesehatan Makassar, 2025)
Nutritional status represents an individual’s overall physical condition, which is influenced by dietary intake and the body’s ability to utilize nutrients efficiently. Among the various determinants, physical activity and fruit–vegetable consumption play essential roles. According to the 2018 Basic Health Research data in Makassar City, the prevalence of nutritional status among adolescents aged 13–15 years was 2.69% severely thin, 7.01% thin, 63.21% normal, 17.67% overweight, and 9.42% obese. This study aimed to analyze the association between physical activity, fruit–vegetable consumption, and nutritional status among 65 female adolescents at SMPN 40 Makassar. Data were collected from November 2024 to February 2025 using a validated Food Frequency Questionnaire (FFQ) for dietary assessment and the International Physical Activity Questionnaire (IPAQ) for activity measurement. Nutritional status was classified based on the Body Mass Index-for-Age (BMI/A) criteria from the World Health Organization (WHO, 2007). Statistical analysis employed the Chi-Square test. The results showed no significant association between physical activity and nutritional status (p = 0.210) nor between fruit–vegetable consumption and nutritional status (p = 0.243). These null findings suggest that other dietary or lifestyle factors, such as total energy intake, meal frequency, or sedentary behavior, may play a more dominant role in determining adolescent nutritional status in urban settings. Future studies are recommended to expand the scope by including multiple determinants of adolescent health and nutrition behaviors